Exploitation and Wear Properties of Nanostructured WC-Co Tool Modified with Plasma-Assisted Chemical Vapor Deposition TiBN Coating - Mateja Šnajdar Musa; Matija Sakoman; Danko Ćorić; Tamara Aleksandrov Fabijanić (Metals, 2021)
In recent years, coated cemented carbides have often been the first choice for a wide variety of tool inserts and applications. Its success as a cutting tool material arises from the unique combination of wear resistance and toughness, and its ability to be formed into complex shapes. The structure obtained by sintering nanoparticle powders provides a significant improvement in product properties, such as higher cutting speeds, lower tool tolerances, and longer service life. In this study, a multi-layered gradient coating, deposited on nanostructured cemented carbides by plasma-assisted chemical vapor deposition (PACVD) was investigated with emphasis on its wear and exploitation properties. TiBN coating was deposited on nanostructured cemented carbide samples with the addition of 5 wt% Co, 10 wt% Co and 15 wt% Co. The samples were consolidated by one cycle hot isostatic pressing (HIP) technique. Complex architecture built of TiN and TiB2 gradient multilayer sequence block was deposited on each type of substrate. Wear resistance of the obtained samples was determined by erosion wear testing and dry sliding wear testing (ball-on-flat test). The friction coefficients of ~0.22 obtained for coated samples by the ball-on-flat test show a decrease in friction when compared to uncoated samples values of ~0.32. The absence of coating rupture was confirmed by wear track depth measurements showing a wear trace depth of ~1.2 μm. Exploitation properties i.e., tool life determination of samples was obtained using single-point turning tool test and compared to commercial cutting tool insert type K10 tested under the same conditions. All the conducted tests show excellent wear and exploitation properties of the newly developed TiBN coating under chosen conditions, including cutting speed, vc = 200 m/min, depth of cut, ap = 1 mm, and feed, fn = 0.2 mm. Coated WC-Co samples with 15 wt% Co, having withstood 15 min of machining with flank wear trace size less than 0.3 mm, suggest significant improvement when compared to trace size of 0.56 mm obtained for K10 commercial cutting insert.